The citizen-makers: Ethical dilemmas in immigrant integration - Liav Orgad (European Law Journal, 2019)
The topic of citizen-making—turning migrants into citizens—is one of the most politically contested policy areas in Europe. Access to European citizenship is governed by national law with almost no EU regulation. The Article brings to the fore normative concerns associated with citizen-making policies in Europe (Section 2). It examines ethical dilemmas involved in the process of creating new citizens (Section 3) and promotes the adoption of a European legal framework on access to citizenship (Section 4). The overall claim is that every newcomer will be required to demonstrate, as a prerequisite for citizenship, attachments to the constitution of the specific Member State, yet the test will be functional, flexible and non-exclusive. As the topic of EU citizenship law is currently at the centre of the European agenda, this article has both theoretical significance and policy implications.
Keywords: 330